Reception of the Western European Cult of Saints Cyril and Methodius on the Example of Papal Documents Grande munus, Egregiae virtutis, Slavorum Apostoli: Description and Analysis - A. M. Lanceva; A. E. Gapanyuk; C. Simon (Концепт: философия, религия, культура, 2021)
The relevance of the given problems is due to the church, state and socio-cultural veneration of the saints Cyril and Methodius as the creators of the Slavic alphabet and translations of the Holy Scriptures and hymnography into the Slavic language, which distinguishes the Slavic world into a separate cultural type, which often interacts with the multicultural paradigm of the modern European paradigm of the civilizational space. A significant place in the article is occupied by the problem of broadcasting the cult of Saints Cyril and Methodius in Catholicism in the coverage of official documents of the Roman Catholic Church, in particular, the encyclical as a separate type of papal documents that correspond to the social concept of the Roman Catholic Church. The purpose of the study is to analyze the encyclicals of the popes Leo XIII and John Paul II in different languages, discovering the general and the particular in their structure, which will serve as an incentive for further interpretation of the cult of the Holy brothers in the Roman Catholic world in the context of the formation of ecumenical communication of Christian churches and interfaith dialogue. The objective of the study is to identify the reception of the cult of Saints Cyril and Methodius in Western Christian religious culture. The novelty of this research is an attempt to analyze and interpret the structure and composition of papal encyclicals and the subsequent identification of the reception of the cult of the saints in Western European religious culture due to the absence of such works in Russian science. The methodological basis of the research is, first of all, an interdisciplinary approach, as well as historical, comparative historical, chronological and textological methods. All analyzed documents raise questions of the primacy of the Pope, missionary work, Catholic piety and the establishment of liturgical veneration of Saints Cyril and Methodius. An analysis of the texts shows the significance of these documents in the context of the formation of the Cyril and Methodius tradition in the West and the dialogue between East and West. The results obtained allow us to speak about the significance of the cult of Saints Cyril and Methodius in the context of individual Slavic countries and the entire Christian world as a whole.